Electrochemical and in-situ spectroelectrochemical properties of novel (5-(tert-butyl)-2-((3,4-dicyanophenoxy)methyl)phenyl)methanolate substituted mononuclear metal phthalocyanines - ORMAN, EFE BATURHAN; ODABAŞ, ZAFER; ÖZKAYA, ALİ RIZA (My University, 2023)
© 2022This work involves the synthesis and characterization of metallic (Co, Fe, Mn, Ni, Zn) ball-type phthalocyanine precursors by using novel 4,4′-(((4-(tert-butyl)-1,2-phenylene)bis-(methylene))bis(oxy))diphthalonitrile starting compound. The classical oxo-bridge in phthalocyanines was altered with the -OCH2- bridge first time for these ball-type phthalocyanine precursors, and the effects of this change on the chemical, physical and spectral features of phthalocyanine complexes were investigated, in the study. The redox properties of phthalocyanines were researched by electrochemical and in situ spectroelectrochemical measurements on a Pt working electrode in non-aqueous medium. The color changes involved in the redox processes were observed via in situ electrocolorimetric techniques. Electrochemical and UV–Vis spectral measurements exhibited that the compounds had reversible and serial one-electron reduction and oxidation processes. Furthermore, they also had nitrile reduction processes because of opened nitrile groups located at peripheral tails of the phthalocyanine complexes. The plentiful redox conducts of the complexes such as Pc ring based and/or central redox active metal-based reduction and oxidation reactions at low potentials showed that these complexes can be used as functional materials. Because of the apparent spectral and net color changes, the complexes are suitable for utilization in electrochromic devices. Moreover, their rich redox features are a sign of their high electrocatalytic activity for oxygen reduction.
Keywords: Kimya; Analitik Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Spektroskopi; İnorganik Kimya; Temel Bilimler; Chemistry; Analytical Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Spectroscopy; Inorganic Chemistry; Natural Sciences; Temel Bilimler (SCI); KİMYA, İNORGANİK VE NÜKLEER; KİMYA, ANALİTİK; SPEKTROSKOPİ; KİMYA, ORGANİK; Natural Sciences (SCI); CHEMISTRY; CHEMISTRY, INORGANIC & NUCLEAR; CHEMISTRY, ANALYTICAL; SPECTROSCOPY; CHEMISTRY, ORGANIC; Fizik Bilimleri; Organik Kimya; İnorganik kimya; Physical Sciences; Organic Chemistry; Ball-type phthalocyanine precursors; Cyclic voltammetry; In situ electrocolorimetry; In situ spectroelectrochemistry; Synthesis